KODE ETIK DAN PENEGAKAN HUKUM DALAM KONTEKS POSITIVISME HUKUM DI INDONESIA - Muhammad Ridwan; Irtiyaj Dwi; Moch.Muzaiyin Afandi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The outline of this research will explain the code of ethics and law enforcement in Indonesia. Codes of ethics not only function as moral and ethical guidelines for professionals, but also as a tool of social control and conflict prevention. Each profession has its own code of ethics that reflects the principles and values specific to that profession. Law enforcement focuses on compliance with applicable laws. Both have the same goal, namely to ensure that members of society or a particular profession behave in a fair and responsible manner. With a code of ethics, public trust will be strengthened, moral integrity will be improved, and law enforcement will become more effective.